1990
DOI: 10.1128/iai.58.12.4016-4019.1990
|View full text |Cite
|
Sign up to set email alerts
|

Hemin levels in culture medium of Porphyromonas (Bacteroides) gingivalis regulate both hemin binding and trypsinlike protease production

Abstract: Washed cells and Sarkosyl-insoluble outer membrane preparations of the black-pigmented bacteroides Porphyromonas gingivalis W50 bound hemin. The amount of hemin removed from a buffered solution by both cells and outer membranes was significantly larger if bacteria had been grown in broths supplemented with 5 mg of hemin per liter rather than none. Conversely, cells grown without supplemental hemin bound relatively little. However, all preparations bound some hemin. In addition, hemin regulated the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Comparison of haem-binding by iron-replete and iron-restricted cells indicated no differences in the quantity of haem bound, suggesting that the additional IROMPs expressed by iron-restricted cells are not involved in haem-binding and that binding of haem compounds and utilization by both iron-replete and iron-restricted bacteria is by a constitutive factor. This is in contrast to the iron-rcgulated haem-binding OMPs of Shigella flexneri and Escherichia coli involved in the uptake and binding of haem (Stugard et al 1989) and a number of putative haem-binding proteins induced under conditions of haem or iron-restriction (Deneer & Potter 1989;Carman, Ramakrishnan & Harper 1990;Otto, Sparrius, Verweij-van Vught & MacLaren 1990;Lcc 1992). In addition, SDS-PAGE of OMP preparations of iron-replete and ironrestricted cells confirms the work of Kay et al (1985) in that the 49-kDa A-layer surface array protein is not an iron-regulated protein.…”
Section: Discussionmentioning
confidence: 95%
“…Comparison of haem-binding by iron-replete and iron-restricted cells indicated no differences in the quantity of haem bound, suggesting that the additional IROMPs expressed by iron-restricted cells are not involved in haem-binding and that binding of haem compounds and utilization by both iron-replete and iron-restricted bacteria is by a constitutive factor. This is in contrast to the iron-rcgulated haem-binding OMPs of Shigella flexneri and Escherichia coli involved in the uptake and binding of haem (Stugard et al 1989) and a number of putative haem-binding proteins induced under conditions of haem or iron-restriction (Deneer & Potter 1989;Carman, Ramakrishnan & Harper 1990;Otto, Sparrius, Verweij-van Vught & MacLaren 1990;Lcc 1992). In addition, SDS-PAGE of OMP preparations of iron-replete and ironrestricted cells confirms the work of Kay et al (1985) in that the 49-kDa A-layer surface array protein is not an iron-regulated protein.…”
Section: Discussionmentioning
confidence: 95%
“…The maximum binding and affinity for hemin was greatest in hemin excess grown cultures, although hemin-limited P. gingivalis expressed novel outer membrane proteins that bind hemin during hemin limitation (49,51,396). Moreover, P. gingivalis W50 grown in hemin excess bound more hemin with a higher affinity than its mutant BEI under the same conditions (64,397). Smalley et al (397) showed that reduced hemin binds to P. gingivalis more than oxidized hemin.…”
Section: Susteninsmentioning
confidence: 99%
“…On the other hand, higher hemin level resulted in elevated cell-associated iron, which increased the capability of the pathogen to survive at times of iron deprivation. It has been speculated that under heminexcessive conditions putative hemin-inducible components might be operative in P. gingivalis and utilized for both hemin binding and transportation of this molecule from the surface of the cell membrane to the cytosolic fraction [43,157,234]. P. gingivalis growth under conditions of heme excess has been reported to enhance the virulence of the bacterium in a murine model of infection [235].…”
Section: Role Of Iron and Heme Capture In The Virulence Of P Gingivalismentioning
confidence: 99%